P110. Networks for semantic integration in auditory speech comprehension. Issue 8 (August 2015) - Klingbeil, J.; Henseler, I.; Wawrzyniak, M.; Wendt, C.; Hartwigsen, G.; Saur, D.
<x xml:space="preserve">Abstract</x> Introduction Semantic integration refers to the influence of previous context on the automatic integration of new information into a sentence during word comprehension. Neuroimaging studies have shown that sentence-level integration of semantic information is associated with activation of a left-lateralized fronto-temporal language network (Baumgaertner et al., 2002). The activation patterns are dependent on the difficulty of semantic integration which can be operationalised on the sentence-level through variation of the terminal word's expectancy, called "cloze probability". With this paradigm we attempted to characterize the properties of the language network relevant for semantic integration through multimodal neuroimaging examining structural and effective connectivity. Methods 17 young and healthy right-handed individuals were examined with functional MRI (fMRI) while they judged aurally presented sentences. Sentences were constructed following the pattern "Der Schreiner baut den … (The Carpenter constructs the …) Tisch (desk = expected)/Turm (tower = unexpected)/Wein (wine = incongruent)/Kirst (pseudo word = anomalous)". In a lexical decision task the subject has to decide if the last word of a sentence is a word ("Tisch"/"Turm"/"Wein") or a pseudo word ("Kirst"). Dynamic causal modeling (DCM) for effective connectivity was calculated for 63 fully connected models between fMRI activation maxima in three regions. Additionally diffusion tensor imaging (DTI) sequences were acquired to assess structural connectivity between these regions. Results Behavioural data show the expected influence of cloze probability on lexical decision reaction times (expected nouns < unexpected nouns < incorrect nouns < pseudo words). For the contrasts unexpected > expected and incorrect > expected activation in the left inferior frontal gyrus (IFG) and the superior and medial temporal gyrus (STG/MTG) was increased (p < 0.001, uncorrected). Activation maxima in anterior IFG (aIFG), anterior MTG (aMTG) and posterior MTG (pMTG) were chosen for evaluation of effective connectivity. Bayesian model selection favoured a fully connected model with a driving input through IFG and showed a task-specific significant increase of inhibitory effective connectivity to the pMTG for higher demands on semantic integration. Specifically, integration of unexpected compared with expected nouns was associated with inhibitory effects of aMTG on pMTG, while higher demands on semantic integration due to presentation of incongruent nouns was associated with an inhibitory effect of aIFG on pMTG. No correlation of variation in effective connectivity and individual reaction times was found. Probabilistic tractography between IFG, aMTG and pMTG from the DTI data set is currently under examination. Discussion These results support the notion of a key contribution of the inferior frontal gyrus and the medial and superior temporal gyrus to semantic integration. DCM network analysis shows inhibitory influences on the pMTG as a consequence of increased difficulty of semantic integration. The functional relevance of these activation patterns and interactions will now be addressed in TMS experiments.